Aplikasi Pembelajaran Bahasa Mandarin Berbasis IOS - Christopher Patrick; Djoni Haryadi Setiabudi; Alexander Setiawan (Jurnal Infra, 2017)
Generally, languages have a role as a means of communication between individuals, because the language serves as a means communication with each other. Mandarin is one of the additional language in knowledge and literature but the lesson that exist has not been effective because of that this application is made. This application will help users who want to learn Mandarin both in writing and reading, such as when users want to learn how to read the mandarin word, write the mandarin word and communicate between users with mandarin language.. Users can learn Mandarin because it has a study feature where the user can learn Mandarin language both how to write and how to read it. Has a test feature where the user is able to test themselves in working on the problems that exist in the application. Users can interact with the same user with the chat feature that has been provided